ACCURATE DETECTION OF VIRAL SEROTYPE DENGUE HEMORRHAGIC FEVER THROUGH AEDES SP MOSQUITOES USING REVERSE TRANSCRIPTASE POLYMERASE CHAIN REACTION (RT-PCR) - Erlin Yustin Tatontos; Fihiruddin Fihiruddin; Nurul Inayati (Poltekkes Kemenkes Semarang, 2021)
Dengue Hemorrhagic Fever (DHF) caused Dengue virus which transmitted through the bite of the Aedes sp. Detection of dengue virus serotypes is essential for epidemiology as well as potential disease pathogens. RT-PCR method was more effective in mosquitoes, because the virus contained in the mosquito body is passed on to the next generation (trans ovarian). The purpose of this research is to know the serotype of DHF virus accurately through vector mosquito using RT-PCR method in Mataram City, so that vector control, early diagnosis and management of DHF disease could be done quickly and precisely. This research was a laboratory explorative research with cross sectional design that determines serotype of DHF virus through vector mosquito using RT-PCR method in Mataram City. The population of this study were Aedes aegypti female mosquitoes from eggs. Collected from houses located in Community Health Center Mataram city worked area with high dengue cases: Pagesangan, Karang Taliwang, Karang Pule, Tanjung Karang, Mataram, and Selaparang especially around the house’s sufferers. The results showed that only the mosquito group from the worked area of the Mataram Community Health Center showed the ribbon image with the base pair in accordance with serotype 1 (DENGUE 1), the other negative.